Responses from writers: depiction of world war I in literature in light of the reading of Eric Maria Remarque, Ernest Hemingway, Wilfred Owen and Siegfried Sassoon - Nawar, Anika (BRAC University, 2017)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2016.